Mechanical and thermal properties of reticulated SiC aerogel composite prepared by template method. (December 2019) - Ye, Xinli; Chen, Zhaofeng; Ai, Sufen; Zhang, Junxiong; Hou, Bin; Zhou, Qianbo; Wang, Fei; Liu, Hezhou; Cui, Sheng
A novel structure-controllable reticulated silicon carbide (SiC) skeleton-reinforced silica aerogel composites (SiC/aerogel) were fabricated successfully by template method. Three-dimensional SiC skeletons prepared by different deposition time were prepared via the chemical vapor deposition technology, and then the silica aerogel was induced by the sol–gel process. The test results showed that the mechanical properties increased and thermal conductivities decreased remarkably after impregnating reticulated SiC skeleton with silica aerogel. The SiC/aerogel-24 possessed the highest compressive strength of 0.82 MPa with the thermal conductivity of 0.1597 W/(m·K) at 600℃, while the SiC/aerogel-12 exhibited the lowest thermal conductivity of 0.1244 W/(m·K) and its compressive strength was 0.64 MPa. The present work reported a novel method to manufacture the structure-controllable reticulated SiC aerogel composite which could be used as a high-temperature super-thermal insulation material for the potential applications.